2016
DOI: 10.1007/s11427-015-4992-3
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterol content and the campesterol:sitosterol ratio influence cotton fiber development: role of phytosterols in cell elongation

Abstract: Phytosterols play an important role in plant growth and development, including cell division, cell elongation, embryogenesis, cellulose biosynthesis, and cell wall formation. Cotton fiber, which undergoes synchronous cell elongation and a large amount of cellulose synthesis, is an ideal model for the study of plant cell elongation and cell wall biogenesis. The role of phytosterols in fiber growth was investigated by treating the fibers with tridemorph, a sterol biosynthetic inhibitor. The inhibition of phytost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…In wild-type cotton, a cohort of genes involved in sterol biosynthesis are highly expressed during early fiber elongation (Supplemental Figure 7). Consistently, sterol is enriched in fibers at the elongation stage compared with the late secondary wall thickening period (Figure 7; Deng et al, 2016). Suppressing GhSCP2D expression downregulated sterol biosynthesis genes and reduced the sterol contents in 5-and 10-DPA fibers compared with wild-type plants (Figure 7), demonstrating a role for GhSCP2D in maintaining sterol homeostasis within the elongating cotton fiber cell.…”
Section: Ghscp2d Is Required For Maintaining Symplasmic Permeability supporting
confidence: 55%
“…In wild-type cotton, a cohort of genes involved in sterol biosynthesis are highly expressed during early fiber elongation (Supplemental Figure 7). Consistently, sterol is enriched in fibers at the elongation stage compared with the late secondary wall thickening period (Figure 7; Deng et al, 2016). Suppressing GhSCP2D expression downregulated sterol biosynthesis genes and reduced the sterol contents in 5-and 10-DPA fibers compared with wild-type plants (Figure 7), demonstrating a role for GhSCP2D in maintaining sterol homeostasis within the elongating cotton fiber cell.…”
Section: Ghscp2d Is Required For Maintaining Symplasmic Permeability supporting
confidence: 55%
“…The top layer of the Zygnema mat investigated in the present study also showed a depletion of β‐sitosterol and campesterol. Both compounds may be incorporated into biomembranes in response to environmental stress (Deng et al ., ). The chlorophyte C .…”
Section: Discussionmentioning
confidence: 97%
“…The top layer of the Zygnema mat investigated in the present study also showed a depletion of β-sitosterol and campesterol. Both compounds may be incorporated into biomembranes in response to environmental stress (Deng et al, 2016). The chlorophyte C. reinhardtii accumulates these metabolites when exposed to high light for a short period of time (Erickson et al, 2015).…”
Section: Cell Wall and Membranementioning
confidence: 99%
“…In fact, genes involved in phytosterol biosynthesis, such as GhSMT2–1 , GhSMT1 , GhCYP51G1 , and GhHYDRA1 , and those involved in BR synthesis or signaling are preferentially expressed in fiber cells, and their expression peaks at the stage of rapid fiber elongation [7, 8, 27–34]. Furthermore, phytosterol levels are at their highest, and the gene encoding the sterol carrier protein ( GhSCP2D ) highly expressed at the fiber elongation stage [4, 12]. Although on gene expression and biochemical aspects, phytosterols are recognized as important factors for the growth and development of cotton fibers, it is unclear what effect of phytosterol content and composition changes on fiber growth.…”
Section: Introductionmentioning
confidence: 99%